Efektifitas Akupresur terhadap Tingkat Kelelahan pada Pasien Kanker yang Menjalani Kemoterapi - Linawati Togatorop; Dudut Tanjung; Wika Hanida Lubis (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to test the effectiveness of acupressure on the fatigue level of cancer patients undergoing chemotherapy. This research method is a quasi-experimental method with a pretest design and a post-test non-equivalent control group design. The sampling technique is a non-probability sampling technique, namely the convenience sampling method. Respondents to this study were cancer patients undergoing chemotherapy at the H. Adam Malik General Hospital in Medan, consisting of 32 respondents for the intervention group and 32 respondents for the control group. The fatigue measurement instrument uses the Brief Fatigue Inventory. Data were analyzed using the Mann-Whitney U test, Chi-Square, and logistic regression. The results showed that the p-value <0.05 and there was no effect of age, anemia, chemotherapy cycles, and cancer stage on the level of fatigue in cancer patients. In conclusion, it is known that acupressure is effective in reducing the level of fatigue in cancer patients undergoing chemotherapy and is recommended as an independent nursing intervention to reduce fatigue in cancer patients. Keywords: Acupressure, Cancer, Chemotherapy, Fatigue.